The Effect of Increasing Fuel Oil on Online Ojek Users - Azizah, Azmy; Maharani, Sonia; Gholib, Iqbal; Putri, Winda (Balai Publikasi Indonesia, 2023)
This study aims to determine the effect of the increase in fuel prices on online motorcycle taxi users. The sample taken in this study was 2% of the student population at the Tarbiyah and Teacher Training Faculty of UIN Sultan Maulana Hasanundin Banten. The sampling technique used in this study was systematic sampling, obtained by distributing questionnaires to respondents via Google forms in the form of a Likert scale and then processed using the SPSS 23 application. The results of this study showed a personal correlation value of 0.696, meaning that the correlation is very high or has a very high relationship. strong and Sig. (2-tailed) of 0.000 <0.005, then Ho is rejected and Ha is accepted, meaning that the effect of the increase in fuel prices on online motorcycle taxi users for students of the Tarbiyah and Teacher Training Faculty of UIN Sultan Maulana Hasanuddin Banten is significant. Based on the R Square value of 0.484, the effect of the increase in fuel prices (variable x) on online motorcycle taxi users (variable y) is 48.4%, while the remaining 51.6% is influenced by other variables not examined